Usefulness of using pure [beta]-TCP bone substitute - Moon, Jeong Eun; Cho, Young Min; Lee, Gwang Chul; Cho, Yong Jin (PloS one, 2025)
The orthopedic implant removal procedure is one of the most commonly performed orthopedic surgeries. This study aimed to compare and report the clinical outcomes between patients who underwent only curettage and those who received pure [beta]-TCP (Neobone.sup.®) following curettage. Between January 1, 2018, and December 31, 2023, patients at our hospital who underwent implant removal and could be followed for over a year were included in the study. The study encompassed 77 cases. The cohort comprised 40 males (51.9%) and 37 females (48.1%) with an average age of 32.5 ± 21.2 years (range 8-69). There were no significant differences between the groups in terms of sex, age, the interval between the first operation and the orthopedic implant removal procedure, locations of operations, or the orthopedic fixation techniques used initially. However, the group undergoing implant removal with [beta]-TCP (Neobone.sup.®) bone graft showed statistically significant improvements in performing scar revision procedures simultaneously and in not requiring drain insertion (p = .000). Compared to the group that only underwent curettage, the group treated with pure [beta]-TCP (Neobone.sup.®) bone graft required fewer drain placements and more often performed scar revisions simultaneously, facilitating faster healing. While there was no difference in the period for ROM exercises or weight bearing, no refractures occurred in the [beta]-TCP bone substitute group. Hence, the application of pure [beta]-TCP (Neobone.sup.®) is clinically advantageous.